2016
DOI: 10.1038/npjbiofilms.2015.27
|View full text |Cite
|
Sign up to set email alerts
|

Not so simple, not so subtle: the interspecies competition between Bacillus simplex and Bacillus subtilis and its impact on the evolution of biofilms

Abstract: Bacillus subtilis biofilms have a fundamental role in shaping the soil ecosystem. During this process, they unavoidably interact with neighbour bacterial species. We studied the interspecies interactions between biofilms of the soil-residing bacteria B. subtilis and related Bacillus species. We found that proximity between the biofilms triggered recruitment of motile B. subtilis cells, which engulfed the competing Bacillus simplex colony. Upon interaction, B. subtilis secreted surfactin and cannibalism toxins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 68 publications
4
62
2
1
Order By: Relevance
“…Surfactin induces potassium‐selective pore formation in the cell membrane (Sheppard et al ., ); moreover, its signalling function is mediated by its toxicity, through the response to potassium leakage (López et al ., ). These properties are also crucial for its non‐signalling roles: surfactin facilitates expansion of the biofilm by lowering surface tension (Angelini et al ., ; van Gestel et al ., ) and may also serve as a means of predation in interspecies competition (Rosenberg et al ., ). It has been suggested that surfactin producers are immune to its effects, as these cells do not differentiate into matrix producers (López et al ., ).…”
Section: The Effect Of Phenotypic State On the Production Of Secretedmentioning
confidence: 97%
See 3 more Smart Citations
“…Surfactin induces potassium‐selective pore formation in the cell membrane (Sheppard et al ., ); moreover, its signalling function is mediated by its toxicity, through the response to potassium leakage (López et al ., ). These properties are also crucial for its non‐signalling roles: surfactin facilitates expansion of the biofilm by lowering surface tension (Angelini et al ., ; van Gestel et al ., ) and may also serve as a means of predation in interspecies competition (Rosenberg et al ., ). It has been suggested that surfactin producers are immune to its effects, as these cells do not differentiate into matrix producers (López et al ., ).…”
Section: The Effect Of Phenotypic State On the Production Of Secretedmentioning
confidence: 97%
“…Cannibalism has been considered a pathway by which cells which have not yet sporulated may defer committing to sporulation by accruing nutrients from lysed neighbouring cells (López et al ., ). The cannibalism toxins have also been proposed to have a role in interspecies competition, along with surfactin (Rosenberg et al ., ). Similarly to surfactin, these toxins can serve to eliminate the most vulnerable cells.…”
Section: The Effect Of Phenotypic State On the Production Of Secretedmentioning
confidence: 97%
See 2 more Smart Citations
“…108 Bacilli are capable of degrading organic materials, ammonia, sulfides, and more, 109 and some are capable of producing surfactants which can disrupt a variety of biological and synthetic oils. 106,111,112 They may also compete with other common environmental bacteria and fail to persist on a surface, 113 potentially requiring continuous or frequent application. 106,111,112 They may also compete with other common environmental bacteria and fail to persist on a surface, 113 potentially requiring continuous or frequent application.…”
Section: Pro -Microb Ial Cle Aningmentioning
confidence: 99%